Creatine Kinase Activity and Malondialdehyde in the Seminal Plasma of Normospermic Infertile Males - Alani, Ghassan T.; El Yaseen, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Normospermia might be a major problem to the doctor and the infertile couple because the male seminal sample has an accepted seminal parameters during the routine seminal examination and the female partner will be claimed for the infertility and she will suffered from coasty, painful, time consuming, non indicated investigations and treatments. Our purpose was to measure sperm creatine phosphokinase (CK) activity, which reflects cytoplasmic retention in immature spermatozoa and malondialdehyde in the seminal plasma which is a marker of oxidative stress in normospermic infertile males' seminal samples.Patient and methods: Nine infertile men with aberrantly normal standard seminal analysis parameters where included in this study and fifteen fertile men samples where used as control. The seminal kinase and seminal malondialdehyde were calculated in addition to the standard seminal analysis.Results: significant higher levels of creatine kinase and malondialdehyde in the normospermic infertile samples (p=0.0001; p=0.006 respectively) and also significant positive correlation between the seminal creatine kinase and seminal malondialdehyde (p=0.001; r=0.613). These markers did not correlate with the percentage of mid piece abnormalities in the studied samples.Conclusion: The seminal plasma creatine kinase and seminal malondialdehyde might be accepted methods to differentiate infertile samples from healthy despite the presence of accepted ranges of standard seminal analysis.